Assessing disease phenotypes in Behçet’s syndrome: insights from a multiple correspondence analysis - Rosaria Talarico; Federica Di Cianni; Federica Di Cianni; Antonello Sulis; Diana Marinello; Valentina Lorenzoni; Marta Mosca (Frontiers in Immunology)
IntroductionBehçet’s syndrome (BS) is a rare systemic vasculitis. Clinical manifestations in BS are frequently clustered rather than discrete, and the concept that distinct clinical phenotypes may exist in BS has recently emerged. The aim of the present work was to identify and analyze the disease phenotypes in a monocentric historical cohort of patients with BS.MethodsA total of 202 patients with BS diagnosis followed up at the Behçet Clinic of the Azienda Ospedaliero-Universitaria Pisana were identified, and demographics, clinical, and therapeutic data were retrospectively collected. Pairwise correlation among variables was evaluated by means of Pearson or Spearman correlation coefficient. A multiple correspondence analysis was performed to investigate the possible phenotypes resulting from the different patterns of associations among the demographic and clinical variables.ResultsMost of the patients were female (67%), Caucasian (92%), and HLA-B51 carriers (65.5%). Mean age at disease onset was 30.06 ± 11.39 years, and oral ulcers (OU) and genital ulcers (GU) were the most common manifestations (96% and 61%, respectively). According to bivariate correlation analysis, significant positive correlations were observed between skin lesions and both OU (p = 0.005) and arthritis (p = 0.014), as well as pathergy (p = 0.001), gastrointestinal (GI) symptoms (p = 0.001), and other involvement (fever and serositis) (p = 0.015). Neurological involvement was significantly and positively associated with ocular lesions (p = 0.0114), GI symptoms (p = 0.030), pathergy (rho = 0.147, p = 0.037) and vein thromboses (p = 0.037). Despite the high heterogeneity, four disease phenotypes emerged from the MCA: (A) male Caucasians with greater age at onset and at diagnosis than the median values, with OU and GU, skin lesions, erythema nodosum (EN), arthritis, and GI symptoms; (B) co-existence of benign subset and pathergy; (C) orchitis/epididymitis associated with neurological involvement and ocular lesions; and (D) GI symptoms plus endoscopic lesions, large vessel disease (both arterial and venous), and other involvement.DiscussionThis study provides valuable insights into the possible BS clinical phenotypes, and the results partially agree with previous association studies on European and extra-European cohorts. Observational comparative studies are warranted to assess the response of tailored phenotype-based therapeutic approaches.